The ultrastructural features of the reaction of protein - synthesizing apparatus of follicular cells of the thyroid gland at distant interaction with the tumor. - I. S. Khripkov (Морфологія, 2016)
Background. Long-standing observations among the patients with primary cancer of the thyroid gland show the high risk of primary cancer appearance in other organs. Simultaneously the high risk of the appearance of thyroid gland cancer is observed after the malignant non-thyroid neoplasms. Objective. The purpose of the present investigation was to study the condition and dynamics of changes in the protein-synthesizing apparatus of follicular cell of the thyroid gland during the process of distant interaction with the tumor in the experiment. Methods. As the experimental model of cancer we have used a model of the slightly differentiated solid adenocarcinoma of Guerin. Experiment was carried out on the male Wistar. Rats were divided into 2 groups. First group - control. To the second group - transplanted cells of Guerin's carcinoma by hypodermic injection beside the region of thighs. Results. After 2 weeks of transplanted tumor growth in follicular cells the increase in the free ribosome number is observed, they are localized in the apical and central part of cells. Granular endoplasmic reticulum is represented by cisterns with ribosomes unevenly distributed on their surface. The mutual parallel alignment of the membranes of endoplasmic reticulum is disrupted. These changes could evidence the violations of the direct way of protein synthesis and activation of the intracellular system of thyrocyte restitution. Conclusion. Distant interaction is manifested on the early stage of tumor progression based on changes in the relationship between the free and connected ribosomes in cell cytoplasm with the subsequent development of diffuse changes of the granular endoplasmic reticulum and the disturbance of the synthetic, transport and secretory functions of the cell.